The brain adjusts grip forces differently according to gravity and inertia: a parabolic flight experiment - White, Olivier (Frontiers in Integrative Neuroscience, 2015)
In everyday life, one of the most frequent activities involves accelerating and decelerating an object held in precision grip. In many contexts, humans scale and synchronize their grip force, normal to the finger/object contact, in anticipation of the expected tangential load force, resulting from the combination of the gravitational and the inertial forces. In many contexts, grip force and load force are linearly coupled. A few studies have examined how we adjust the parameters - gain and offset - of this linear relationship. However, the question remains open as to how the brain adjusts grip force regardless of whether load force is generated by different combinations of weight and inertia. Here, we designed conditions to generate equivalent magnitudes of load force by independently varying mass and movement frequency. In a control experiment, we directly manipulated gravity in parabolic flights, while other factors remained constant. We show with a simple computational approach that, to adjust grip force, the brain is sensitive to how load forces are produced at the fingertips. This provides clear evidence that the analysis of the origin of load force is performed centrally, and not only at the periphery.